RANCANG BANGUN APLIKASI E-PROPERTI BERBASIS FRAMEWORK CODEIGNITER - tukino, tukino; Arnomo, Sasa Ani (Computer Based Information System Journal, 2021)
The progress of the internet has become the best means to start a property business and it has been proven to be an effective and effective media of information from the internet to disseminate information that is fully accessible to anyone,anytime and anywhere. The great effect on the property business is caused through the internet because only by accessing it from smartphone device and computers at home or in the office of prospective buyers can see property add information.In today’s digital era property sales are mostly done on social media. Social media has many users. But social media has the disadvantages of having to pay if you want to advertise sales, consumers are only users of social media, sales posts quickly sink. In this research, a web-based property sales and leasing information system will be built to cover the shortage.